Step-by-step explanation:
do u have like a photo or sum to explain it better
(f+g)(x) = f(x) + g(x)
(f+g)(x) = [ f(x) ] + [ g(x) ]
(f+g)(x) = [ 3x-2 ] + [ 2x+1 ]
(f+g)(x) = (3x+2x) + (-2+1)
(f+g)(x) = 5x - 1
Answer is choice B
Answer:
13 in
Step-by-step explanation:
let w be width then length is w + 6
the area (A) of a rectangle is calculated as
A = length × width , then
A = w(w + 6) = 91 , that is
w² + 6w = 91 ( subtract 91 from both sides )
w² + 6w - 91 = 0 ← in standard quadratic form
(w + 13)(w - 7) = 0 ← in factored form
equate each factor to zero and solve for w
w + 13 = 0 ⇒ w = - 13
w - 7 = 0 ⇒ w = 7
however, w > 0 then w = 7
and length = w + 6 = 7 + 6 = 13 in
The cell labelled a is a joint frequency of 48 and the cell labelled b is a marginal frequency of 93.
<h3>What is a frequency table?</h3>
The frequency of an occurrence or a value is the number of times it happens. A frequency table is a list of objects with the frequency of each item shown in the table.
The data is mentioned in the table given below:
We need to find the value of a and b.
Here, Cell Phone+No Cell Phone=Total
To find a:
Add the no lap entries, that is 159+a=207
⇒a=48
To find b:
Add the lap entries, that is 82+11=b.
⇒b=93.
Therefore, the cell labelled a is a joint frequency of 48 and the cell labelled b is a marginal frequency of 93.
To learn more about the frequency table visit:
brainly.com/question/12576014.
#SPJ1